Ferrocene addition for suppression of hydrogen sulfide formation during thermal recovery of oil sand bitumen. (1st September 2021) - Huang, Haiping; Zhang, Hong; Han, Denglin
Abstract: The occurrence of H2 S during thermal recovery production becomes one of the biggest challenges. While various industrial processes can remove H2 S at the surface, to prevent the formation of H2 S in reservoir is much less successful. Ferrocene was chosen as the likely target reagent after a review of iron compound volatility and environmental considerations. To evaluate this, closed system gold tube pyrolysis experiments were conducted on an Athabasca oil sand at 350–650 °C to examine gas compositions with and without ferrocene addition. Slightly higher hydrocarbon gas yields have been observed from samples with ferrocene addition likely caused by ferrocene decomposition. Yields of carbon dioxide (CO2 ) are higher in plain oil sand samples before 550 °C but the trend was reversed afterwards with more CO2 being generated from ferrocene addition ones. H2 S yields in samples without ferrocene increase from background value at 350 °C to the highest amount at 450 °C then disappear above 625 °C. Thermal decomposition of organosulfur compounds is supposed to be the main route for the occurrence of H2 S in the sulfur-rich bitumen pyrolysis. Ferrocene is proved to be powerful H2 S removal reagent as no H2 S can be detected from ferrocene addition samples. The reactions of ferrocene with H2 S may form iron sulfides, cyclopentadiene and hydrogen. Complete, rapid, and predictable reactions and inert reaction products make ferrocene as an ideal in situ H2 S scavenger, while the potential for the deposition of metal sulfides may reduce the permeability. Ferrocene is widely available for industry, however, the unit cost has not been assessed in this study. Highlights: Gold tube pyrolysis of oil sand bitumen yields various hydrocarbon and nonhydrocarbon gases. H2 S was generated in plain oil sand pyrolysis but dismissed with ferrocene addition. Thermal decomposition of organosulfur compounds is attributed to the occurrence of H2 S. Ferrocene was proposed as a vapor phase transported reagent for in situ H2 S suppression.